Management of elderly patients with advanced infiltrating and metastatic bladder cancer: an oncogeriatric approach. (June 2011) - Droz, Jean-Pierre; Boyle, Helen; Flééchon, Aude; Terret, Catherine
Bladder cancer is the fourth most common cancer in men older than 70 years. Muscle-infiltrating tumors can be cured by radical cystectomy but are associated with poor prognosis. Metastatic disease is not curable. The purpose of this article is to critically review the knowledge available on bladder cancers in elderly patients. We reviewed the recent literature on bladder cancer in the elderly, as well as updated concepts in geriatric oncology. The oncogeriatric setting was specifically explored. There is a large and growing body of research literature on infiltrating bladder cancers. Nevertheless only age and, in some instances, comorbidities are analyzed, whereas the different geriatric domains are generally overlooked. Whereas it is possible to draw conclusions on incidence, medical practice and complications of radical cystectomy in elderly patients, none of these allow a clear decision-making strategy to be defined. In metastatic disease, only a few articles have addressed the question of the specific management of elderly patients, principally because this population is considered to be unfit for cisplatin-based chemotherapy. None of the specific oncogeriatric domains has been extensively studied. Specific prospective studies should be designed to explore oncogeriatric domains, for example dependence, nutrition, cognition, thymic evaluation, comorbidities, polypharmacy and psychosocial evaluation. In infiltrating bladder cancer, these studies should be based on prospectively followed patient cohorts. In metastatic disease, specific prospective trials involving geriatric screening and/or comprehensive geriatric assessment are needed.